Development of Nitrile Butadiene rubber-based coating material using waste tire powder for gasket application - Chai, Kah Siong (2023)

(untitled)
The study of replacement of carbon black with waste tire powder in a formulation to avoid usage of carcinogenic and high agglomerate filler and waste tire powder is a initiate of cost saving and environment friendly. Thus, a new gasket coating material has been developed using nitrile butadiene rubber (NBR) as the matrix and waste tire powder (WTP) as the filler to replace commercially used carbon black through solution mixing method. The formulation optimization was done by manipulating the loading of WTP, dioctyl phthalate (DOP) used as plasticizers, and sulphur as the curing agent. Different loading of compounding and manipulation has been study in this experiment such as 80phr and 90phr for WTP, 10phr and 15phr for DOP, and 1phr and 2phr for sulphur. Upon compounding, the processing parameters such as foaming and curing time and temperatures were optimized. The coating solutions with different compounding formulation undergoes foaming at different temperature of 70oC and 80oC for 20 mins, followed by curing at 130oC for 30 mins and 40 mins. Characterisation and mechanicals testing were conducted to study the processability, mechanical properties, thermal stability, oil absorption, solvent fraction, and the hardness of the coating materials to determine the suitability of WTP as the filler for NBR. The experimental result show that formulation D10- ii W90-S2 (A) is the most optimum and suitable for gasket making. The formulation with higher filler and sulphur loading can form a barrier and entanglement to minimize the oil absorption intake and gel fraction. The formulation D10-W90-S2 (A) has 16.01% of mass increase which comply with the oil absorption tolerance and 14.02% of mass changes in solvent fraction. Furthermore, the thermal aging test shows that D10-W90-S2 (A) is most stable formulation as it has the lowest variance before and after thermal aging test. The gasket is heated under 1500C for thermal aging test and follow up with oil absorption test for further justification. The result shows that formulation D10- W90-S2 (A) has comparative mass changes under aged and unaged gasket. The aged gasket has mass increase of 16.52% while unaged gasket has 16.01%. Besides, the three least formulations from oil absorption were selected and repeated with rolling process. The comparison of rolling and casting shown that casting specimens has better mechanical properties as compared to rolling. The occurrence of shear strain during rolling process results in the destruction of the foam structure and reduction in mechanical properties. D10-W90-S2 (A) has the least oil absorption of 17.13% as compared to D10-W90-S1 (C), and D15-W80- S2 (C) which had 26.32% and 22.33% respectively. However, gasket produced through casting method has lower oil absorption as compared to those produced through rolling method. Thus, casting method is more preferable as compare to rolling method.